Improving Students' Writing Skills in Grade IV of SDN 173274 Siborongborong Through a Contextual Approach - Siregar, Christyani; Tambunan, Yusniar N (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to improve students' interest and writing skills with a contextual approach. This research is a Class Action Research that takes place in grade IV of SD Negeri 173274 Siborongborong. This research was carried out in three cycles. Teachers and researchers prepare the lesson plan for each Cycle. Each action consists of four stages: planning, action, observation, and reflection. The data collection techniques are questionnaires, observations, interviews or discussions, document reviews, and tests. The validity of the data in this study was tested by triangulation and review of key informants. The results of the study can be concluded as follows: First, the application of a contextual approach can increase students' interest in writing, and it can be seen that after taking action, students make plans before writing, revise after selecting writing, use Enhanced Spelling and prefer to practice writing even though the teacher does not order them. Second, a contextual approach can improve students' writing skills from 63.01 to 86.53.